The Effect of Current Ratio and Debt to Equity Ratio on Return on Assets in Food Sub Sector Companies and the Beverages Listed in Indonesian Stock Exchange 2018-2022 - Syarif, Abdul Hamid; Murdiansyah, Isnan (PT FORMOSA CENDEKIA GLOBAL, 2024)
The study investigates the impact of financial ratios on the profitability of food and beverage companies listed on the Indonesia Stock Exchange (IDX) between 2018 and 2022. Hypothesis testing indicates that neither the Current Ratio (CR) nor the Debt to Equity Ratio (DER) exert a statistically significant influence on Return on Assets (ROA) when considered individually. These findings imply that other variables, potentially beyond liquidity and capital structure, may have a more substantial effect on profitability. Future research should consider examining broader determinants such as managerial practices and market dynamics to attain a holistic understanding of profitability drivers. Employing longitudinal studies and incorporating a larger, more diverse sample size could enhance the robustness and generalizability of the research, offering valuable insights for industry stakeholders and academics.